Magnetically controlled growing rods in the treatment of early onset scoliosis: A single centre experience of 44 patients with mean follow-up of 4.1 years. (July 2020) - Abdelaal, A.; Munigangaiah, S.; Trivedi, J.; Davidson, N.
No abstract available